Composition and regulation of the immune microenvironment of salivary gland in Sjögren’s syndrome - Tan, Zhen; Wang, Li; Li, Xiaomei (Frontiers in Immunology, 2022)
Primary Sjögren’s syndrome (pSS) is a systemic autoimmune disease characterized by exocrine gland dysfunction and inflammation. Patients often have dry mouth and dry eye symptoms, which seriously affect their lives. Improving dry mouth and eye symptoms has become a common demand from patients. For this reason, researchers have conducted many studies on external secretory glands. In this paper, we summarize recent studies on the salivary glands of pSS patients from the perspective of the immune microenvironment. These studies showed that hypoxia, senescence, and chronic inflammation are the essential characteristics of the salivary gland immune microenvironment. In the SG of pSS, genes related to lymphocyte chemotaxis, antigen presentation, and lymphocyte activation are upregulated. Interferon (IFN)-related genes, DNA methylation, sRNA downregulation, and mitochondrial-related differentially expressed genes are also involved in forming the immune microenvironment of pSS, while multiple signaling pathways are involved in regulation. We further elucidated the regulation of the salivary gland immune microenvironment in pSS and relevant, targeted treatments.